2001
DOI: 10.1108/02686900110385669
|View full text |Cite
|
Sign up to set email alerts
|

Association of audit delay and audit firms’ international links: evidence from Bangladesh

Abstract: Examines whether audit delay of Bangladeshi companies is associated with audit firms’ links with international firms. The study is based on a sample of 115 listed companies of the Dhaka Stock Exchange for the year ended 1998. A non‐parametric tool has been used to find whether any significant difference exists among audit firms. The results of previous studies on audit delay show that firms associated with international audit firms appear to provide motivation for shorter audit delays. However, this study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…The socio-economic environment is affected by unsatisfactory legal enforcement and poor working conditions. In addition, the Bangladesh corporate and economic environment also suffers from lack of timely information (Imam et al, 2001), and political instability (CPD, 2003). 7 This is consistent with Farooque et al (2007), who report that some of the institutional features of Bangladesh include a less developed capital market, an at least weak-form efficient stock market, absence of an active market for corporate control, generally concentrated ownership, high reliance on bank financing and a passive managerial labour market.…”
Section: Excess Liquidity In the Banking Sectormentioning
confidence: 99%
“…The socio-economic environment is affected by unsatisfactory legal enforcement and poor working conditions. In addition, the Bangladesh corporate and economic environment also suffers from lack of timely information (Imam et al, 2001), and political instability (CPD, 2003). 7 This is consistent with Farooque et al (2007), who report that some of the institutional features of Bangladesh include a less developed capital market, an at least weak-form efficient stock market, absence of an active market for corporate control, generally concentrated ownership, high reliance on bank financing and a passive managerial labour market.…”
Section: Excess Liquidity In the Banking Sectormentioning
confidence: 99%
“…The issue of audit report timeliness has been investigated for the past 30 years. The evidence documented from the data of different countries, includes developed countries like the US (Ashton, Willingham and Elliot, 1987), New Zealand (Carslaw and Kaplan, 1991), Hong Kong (Jaggi and Tsui, 1999), Canada (Ashton, Graul and Newton, 1989), France (Soltani, 2002), Australia (Dyer and McHugh, 1975), the UK (Abdelsalam and Street, 2007), Spain (Bonsón-Ponte, Escobar-Rodríguez and Borrero-Domínguez, 2008) as well as developing countries such as Zimbabwe (Owusu-Ansah, 2000), Bangladesh (Iman, Ahmed and Khan, 2001), Bahrain (Khasharmeh and Aljifri, 2010), Egypt (Ezat and El-Masry, 2008;Afify, 2009), Malaysia (Che-Ahmad and Abidin, 2008) and the United Arab Emirates (Khasharmeh and Aljifri, 2010). Studies on audit timeliness are frequently centred to ascertain the determinants of the audit report lag.…”
Section: Audit Delaymentioning
confidence: 99%
“…The result revealed that statistically significant differences existed among companies in terms of their disclosure scores, assets sizes, tumover or .lales, and Debt-equity ratios. They found that in terms of disclosure scores, Indonesian companies (46) disclosed significantly less than Malaysian (87), Singaporean (103) and Thai companies (66). Philippine companies (62) disclosed significantly less than companies in Malaysia (87) and Singapore (103), while Thai companies (66) disclosed significantly less than those in Singapore (103).…”
Section: The Current Status Of the Banking Sectormentioning
confidence: 99%